Vitamin D and allergic diseases - Zhang, Panyu; Xu, Qingxiu; Zhu, Rongfei (Frontiers in Immunology, 2024)
In recent years, the relationship between vitamin D and allergic diseases has received widespread attention. As a fat-soluble vitamin, vitamin D plays a crucial role in regulating the immune system and may influence the onset and progression of diseases such as atopic dermatitis, allergic rhinitis, and asthma. To understand the underlying mechanisms, we have summarized the current research on the association between vitamin D and allergic diseases. We also discuss the impact of vitamin D on the immune system and its role in the course of allergic diseases, particularly focusing on how vitamin D supplementation affects the treatment outcomes of these conditions. We aim to provide a theoretical basis and practical guidance for optimizing the management and treatment of allergic diseases by modulating vitamin D levels.